Fluid and electrolyte balance in ultra-endurance sport - Rehrer, N. J. (Sports Medicine, 2001)
It is well known that fluid and electrolyte balance are critical to optimal exercise performance and, moreover, health maintenance. Most research conducted on extreme sporting endeavour (>3 hours) is based on case studies and studies involving small numbers of individuals. Ultra-endurance sportsmen and women typically do not meet their fluid needs during exercise. However, successful athletes exercising over several consecutive days come close to meeting fluid needs. It is important to try to account for all factors influencing bodyweight changes, in addition to fluid loss, and all sources of water input. Increasing ambient temperature and humidity can increase the rate of sweating by up to approximately 1 L/h. Depending on individual variation, exercise type and particularly intensity, sweat rates can vary from extremely low values to more than 3 L/h. Over-hydration, although not frequently observed, can also present problems, as can inappropriate fluid composition. Over-hydrating or meeting fluid needs during very long-lasting exercise in the heat with low or negligible sodium intake can result in reduced performance and, not infrequently, hyponatraemia. Thus, with large rates of fluid ingestion, even measured just to meet fluid needs, sodium intake is vital and an increased beverage concentration [30 to 50 mmol/L (1.7 to 2.9 g NaCl/L) may be beneficial. If insufficient fluids are taken during exercise, sodium is necessary in the recovery period to reduce the urinary output and increase the rate of restoration of fluid balance. Carbohydrate inclusion in a beverage can affect the net rate of water assimilation and is also important to supplement endogenous reserves as a substrate for exercising muscles during ultra-endurance activity. To enhance water absorption, glucose and/or glucose-containing carbohydrates (e.g. sucrose, maltose) at concentrations of 3 to 5% weight/volume are recommended. Carbohydrate concentrations above this may be advantageous in terms of glucose oxidation and maintaining exercise intensity, but will be of no added advantage and, if hyperosmotic, will actually reduce the net rate of water absorption. The rate of fluid loss may exceed the capacity of the gastrointestinal tract to assimilate fluids. Gastric emptying, in particular, may be below the rate of fluid loss, and therefore, individual tolerance may dictate the maximum rate of fluid intake. There is large individual variation in gastric emptying rate and tolerance to larger volumes. Training to drink during exercise is recommended and may enhance tolerance.